Teaching Technical Skills in Sericulture - G Srinivasa,; V.K Rahmathulla,; M.T Himantharaj,; G.S Vindhya,; R.K Rajan, (Journal of Agricultural Extension Management, 2025)
The Central Sericultural Research and Training Institute, Mysore, Karnataka offers a training course for extension staff to effectively transfer the technology in the field and the sericulturists to set up and look after their own silkworm rearing programmes. The course generally consists of 50 per cent of theory inputs and 50 per cent of practical inputs (teaching skills / practical sessions). During the course, the participants have to attend to silkworm rearing under the supervision of experienced trainers in the morning and evening hours for a period of one hour in the early stages of silkworm to 2 hours in the later stages. They may have to spend the entire day sometimes during silkworm spinning stage to deliver the matured larvae to mountages for spinning. The participants also attend the theory classes, which enable them to blend their skills learnt during rearing